Thermo-resistive and thermo-piezoresistive sensitivity of carbon nanostructure engineered thermoplastic composites processed via additive manufacturing - Pawan Verma; Andreas Schiffer; S. Kumar (Polymer Testing, 2021)
We experimentally examine the thermo-resistive and thermo-piezoresistive sensitivity of multiwall carbon nanotube (MWCNT)/polypropylene random copolymer (PPR) nanocomposites processed via fused filament fabrication (FFF) process. The filament feedstocks were fabricated by melt blending of neat PPR with a predetermined amount of MWCNTs (either 4, 6 or 8 wt%) using a twin-screw extruder. Thermo-resistive characteristics of MWCNT/PPR composites were measured under both constrained and unconstrained heating from approximately 30-100 °C. For all MWCNT concentrations considered here, negative temperature coefficients of resistivity (TCR) were observed for both constrained and unconstrained heating, as a consequence of thermal fluctuation-induced tunneling at MWCNT junctions. The highest thermo-resistive sensitivity was measured for the composite with the lowest MWCNT concentration (4 wt%) under unconstrained conditions, reporting a TCR of −12,800 × 10−6/°C, which is higher in magnitude than that of other polymer nanocomposites reported in the literature. Moreover, the MWCNT/PPR composites exhibit strong thermo-piezoresistive response under tensile loading. For 4 wt% MWCNT loading, the gauge factor (measured over 0–20% strain range) of the composite increased from 27.8 to 52.3 when the temperature was raised from 30 °C to 60 °C. Our results further evince higher thermo-piezoresistive sensitivity i.e., a gauge factor as high as 395 at 60 °C. The electron tunneling and hopping, both thermally-assisted and activated by mechanical deformation of the PPR matrix, significantly increase the thermo-piezoresistance with the increase in temperature in this range. The excellent thermo-resistive and thermo-piezoresistive characteristics of MWCNT/PPR composites reported in this study would enable the development of smart nanocomposites for self-sensing both temperature and strain/damage state.